An Analysis of Verbal and Non-Verbal Signs in Rexona Clinical Protections Advertisement - I Made Tobi Arinata; Desak Putu Eka Pratiwi; I Komang Sulatra (Austronesian: Journal of Language Science & Literature, 2022)
Humans interact using verbal and nonverbal communication tools, such as messages, pictures, sounds, and gestures. This study is intended to examine the connotative and denotative meanings of verbal and nonverbal signs in the “Rexona Clinical Protection” advertisement. The study is designed with a qualitative approach. The observation method was used in collecting the data. The data was obtained from the website Rexona. There are three items of the data analysis, namely verbal and nonverbal signs analyzed based on Saussure’s semiotic theory, and the meaning of the verbal and nonverbal signs was analyzed using Barthes’s theory. Wierbicka’s color theory lends support to the denotative and connotative meanings. As a result, the writer discovered six verbal and six nonverbal signs in this advertisement. Advertisers highlight the products in this advertisement, attempting to persuade viewers that using “Rexona Clinical Protection” products is one of the most important things we can do to protect our bodies from body odor and excessive sweating. From this analysis, it can be concluded that the “Rexona Clinical Protection” advertisement uses meaningful sentences to attract the attention of its target consumers.